Translation as Experimentalism Exploring Play in Poetics - King Lee, Tong (Social Sciences, 2022)
This Element argues for a perspective on literary translation based around ludification, using concrete poetry as a test case. It questions assumptions about translatability and opens up the discursive space of literary writing to transgressive articulation and multimodal performance. This title is also available as Open Access on Cambridge Core.